RESULTS OF CONCOMITANT PHOTON-NEUTRON THERAPY IN THE PALLIATIVE TREATMENT OF METASTATIC BRAIN TUMORS ACCORDING TO THE DATA OF THE CHELYABINSK REGIONAL CLINICAL ONCOLOGY DISPENSARY - G. G. Bobkova; A. V. Vazhenin; E. Yu. Kandakova; A. I. Kuznetsova; I. A. Vazhenin; Z. Z. Munasipov (Опухоли головы и шеи)
The authors analyzed the long-term results of standard radiotherapy (RT) in 153 patients and those of concomitant photon-neuron therapy (CPNT) in 24 patients in the combined treatment programs. The use of densely ionizing radiation in combined palliative programs for radio-resistant tumors, that include brain metastases, increased survival and improved quality of life. The survival after CPNT was 10–24 months in all the treatment programs: in the control group, that after RT and combined treatment was 4–6 and 7–11 months, respectively.